2013
DOI: 10.1152/ajpendo.00191.2013
|View full text |Cite
|
Sign up to set email alerts
|

QRFP induces aldosterone production via PKC and T-type calcium channel-mediated pathways in human adrenocortical cells: evidence for a novel role of GPR103

Abstract: Randeva HS. QRFP induces aldosterone production via PKC and T-type calcium channel-mediated pathways in human adrenocortical cells: evidence for a novel role of GPR103. Am J Physiol Endocrinol Metab 305: E1049 -E1058, 2013. First published August 20, 2013; doi:10.1152/ajpendo.00191.2013.-Hormonal regulation of adrenal function occurs primarily through activation of GPCRs. GPCRs are central to many of the body's endocrine and neurotransmitter pathways. Recently, it was shown that activation of GPR103 by its li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…In humans and rodents, 43RFa, 26RFa, and GPR103 are mainly expressed in brain, particularly in the hypothalamus (8), as well as in peripheral tissues, including the eye, testis, thyroid, adipose tissue, and macrophages (6,(9)(10)(11). 43RFa and 26RFa have been implicated in many physiological functions, including stimulation of food intake (5,(12)(13)(14)(15)(16)(17), regulation of gonadotropic axis (18,19), aldosterone secretion (7,20), bone formation (21), adipogenesis and inflammation (10,11), blood pressure (12), and prostate cancer differentiation and migration (22).…”
mentioning
confidence: 99%
“…In humans and rodents, 43RFa, 26RFa, and GPR103 are mainly expressed in brain, particularly in the hypothalamus (8), as well as in peripheral tissues, including the eye, testis, thyroid, adipose tissue, and macrophages (6,(9)(10)(11). 43RFa and 26RFa have been implicated in many physiological functions, including stimulation of food intake (5,(12)(13)(14)(15)(16)(17), regulation of gonadotropic axis (18,19), aldosterone secretion (7,20), bone formation (21), adipogenesis and inflammation (10,11), blood pressure (12), and prostate cancer differentiation and migration (22).…”
mentioning
confidence: 99%
“…However, it is unclear whether endogenous QRFP stimulates the HPA axis in vivo. Both Gpr103 and QRFP are primarily localized in human and rat adrenal cortex [7,9]. QRFP stimulates cortisol secretion as well as induction of key steroidogenic enzymes in human adrenocortical cells [7].…”
Section: Discussionmentioning
confidence: 99%
“…QRFP has orexigenic effects in rodents [1][2][3][4][5]. QRFP also regulates behavioral arousal, blood pressure, locomotor activity, and aldosterone and insulin secretion [2,6,7]. QRFP acts via a specific receptor, Gpr103, which belongs to the G proteincoupled receptor superfamily [2,8].…”
mentioning
confidence: 99%
“…Previous results suggested that QRFPR is coupled to a Gi/0 and/or to a Gq protein (Fukusumi et al 2003). Furthermore, it has been reported that 26RFa/QRFP enhances corticosteroid secretion in human adrenocortical cells by regulating key steroidogenic enzymes involving MAPK/PKC (mitogen-activated protein kinase/protein kinase C) and Ca 2+ (calcium ions) signaling pathways via QRFPR (Ramanjaneya et al 2013).…”
Section: Introductionmentioning
confidence: 99%